An overview: Natural fiber reinforced hybrid composites, chemical treatments and application areas. (2020) - Karthi, N.; Kumaresan, K.; Sathish, S.; Gokulkumar, S.; Prabhu, L.; Vigneshkumar, N.
Abstract: Application of natural fibre reinforced polymer composites (NFPC) in transportation diligences has become inexorable due to light weight, superior properties, less cost of production and suitability to many products. But the main disadvantages of employing these fibers are their poor dimensional stability and high hydrophilic nature. Interfacial bonding between the fiber and matrix plays a vital role in deciding the mechanical characteristics of composites. Various chemical cures are applied for enhancing the fiber-matrix adhesion which ends up in better mechanical characteristics of the composites. The current aerospace and automotive industries are looking to change the conventional materials which are high density material to composite material for reducing the overall weight of the vehicle to increase its performance. This review paper provides a vast overview on natural fiber reinforced composites, various chemical treatments applied and applications of those composites.